Instantiating the creation process in digital art for serious games design - Marcos, Adérito Fernandes (2011)
The creation process in digital art relies often on collaborations between an artist (or group of artists) and a multidisciplinary team. This collaboration implies a multidisciplinary work involving art, science, technology, design, psychology, etc. that come together by sharing a common communicational and informational space. In this essay we bring into discussion how the creation process cycle in digital art could be instantiated and applied for the development of serious games through end-user purposes of both creative authors: the digital artists and the serious games developers. We realise a comprehensive analysis of this creation process in digital art, specially the aesthetic musing activity, while devising how it could be helpful to introduce new engaging stimulus in the creative process of serious games.